Digitalization of Building Site Management in the Construction Industry - Ça?atay Takva; Jan Cudzik; Zeynep Ye?im ?lerisoy (International Journal of Sustainable Construction Engineering and Technology, 2023)
With Industry 4.0, a digital transformation has started in the construction industry. However, 4.0 technologies have difficulties in the integration of digital systems due to the diversity and complexity of the processes in the construction industry. Multidisciplinary work in architectural projects and the need for high productivity require digital renovation planning in the construction industry. The application of the technologies that emerged because of digital transformation on the building site has revealed the concept of the smart building site. Within the framework of many current issues such as the smart building site, the digital transformation on the building sites needs to be explored and defined. In this study, a bibliometric analysis was carried out on the publications in this field by evaluating the transformation potentials of the digitalized building sites of the future. Academic publications that will raise awareness in the improvement of building site management and the development of digital systems have been determined. Conceptual integrity was created by seeing the research gap for digitalization in building site management and it was aimed to guide researchers in future studies. As a result, based on the research area analysis and the diversity of academic publications, it was seen that the studies in the field of architecture were insufficient compared to the engineering fields.